Choosing terror : virtue, friendship, and authenticity in the French Revolution - Linton, Marisa, 1959- (Oxford University Press, 2013)
'Choosing Terror' examines the leaders of the French Revolution and particularly the process whereby they came to choose terror. Exploring the politics against a backdrop of traumatic events wars and betrayals it portrays the Jacobins as complex people who were influenced by emotions and personal loyalties, as well as by ideology.